The pattern and characteristics of sexual assault perpetrators and survivors managed at a sexual assault referral centre in Lagos - Oluwajimi O. Sodipo; Ayoade Adedokun; Adedeji O. Adejumo; Olushola Olibamoyo (AOSIS, 2018)
Background: There has presumably been an increase in cases of sexual assault in Nigeria; however, accurate data on the characteristics of the survivors and perpetrators are not readily available in most cases. Aim: To report the pattern and characteristics of sexual assault perpetrators and survivors managed at the Mirabel Centre, Lagos State University Teaching Hospital (LASUTH), Ikeja - a three-year review. Methods: A retrospective audit carried out in the sexual assault referral centre (SARC) - Mirabel Centre, LASUTH, Lagos State, Nigeria. A total of 2160 case files from July 2013 to January 2017 were assessed for age group of survivors and gender, among others. Results: A total of 2160 cases were analysed. The mean age of survivors was 13.9 (± 4.4) years with the 11-20 years age group having the highest number of survivors (48.4%) and the 0-10 years age group having 35.9% of survivors. Majority of the survivors (97.7%) were female. The majority of the perpetrators were known to the survivors with 10.3% being family members. Defilement (71.6%) was the most reported type of assault at the centre with rape (20.3%) being the second most common. The majority of the referrals to the centre were from the police (76.7%), while self-referrals made up 8% of referrals. Conclusion: Minors and adolescents formed the majority of the survivors. Defilement was the most reported form of sexual violence. There needs to be special intervention for better monitoring and protection of minors and youths against sexual assault. The establishment of more sexual assault referral centres in Nigeria will increase reportage and treatment of survivors.